Analisis Kepuasan Pengguna Sistem Informasi Tata Usaha (SITU) Pada Universitas Negeri Gorontalo - Rizan Machmud (Jurnal Manajemen, 2014)
The research aims to find out the partialinfluence (system quality and information quality) of users’ satisfaction on administration information system.